Fluorogenic probe for measuring high-mannose type glycan-specific endo-β-N-acetylglucosaminidase H activity. Issue 13 (1st July 2019) - Ishii, Nozomi; Sano, Kanae; Matsuo, Ichiro
Graphical abstract: Abstract: We synthesized a fluorogenic probe with a high-mannose type heptasaccharide structure to detect the hydrolytic activity of endo-β- N -acetylglucosaminidase from Streptomyces plicatus (Endo-H). The heptasaccharide derivative (1 ) was labeled with an N -methylanthraniloyl group as a reporter dye at the branching point of the β-mannoside residue and 2, 4-dinitrophenyl group as a quencher molecule at the reducing end, which was hydrolyzed by Endo-H, resulting in increased fluorescence intensity. Thus, Endo-H activities could be evaluated easily and quantitatively by measuring the fluorescence signal. Using both this probe (1 ) and a previously synthesized pentasaccharide probe, the hydrolysis activity of Endo-H and Endo-M were investigated. The results clearly showed a correlation with the substrate specificity of each enzyme.